Examining and Comparing the Degree of Attention to Phenomenological Identity Components in Upper Secondary Biology Textbooks Based on Shannon Entropy Method - Hatami, Hakimeh; Baghaei, Hossein; Hojjati, Seyyed Abdullah (Assessment and Practice in Educational Sciences, 2025)
Learning and teaching biology in schools is a cultural necessity for the modern world, and with the help of phenomenology, we can gain a more precise view of the aspects and moments that occur within the teaching process. The present study was conducted with the aim of examining and comparing the degree of attention given to phenomenological identity components in upper secondary biology textbooks. This study is applied in terms of purpose and falls under the category of content analysis research in terms of data collection. The method employed was content analysis using the Shannon entropy approach. In this technique, the frequency of each of the 29 components of phenomenological identity in upper secondary biology textbooks was first determined, after which the frequencies were normalized. Based on these normalized data, the information load and importance coefficient for each phenomenological identity component were calculated. The analysis of upper secondary biology textbooks showed that the component related to challenge acceptance had the highest frequency with 109 instances, while the lowest frequencies were observed for the components of being directional, being strong, being profound, guidance and leadership, self-esteem, satisfaction, and pluralism, each with a frequency of (0). Furthermore, the highest importance coefficient among the phenomenological identity components in the textbooks was related to the components of life in the classroom and communication skills with a value of 0.215. The lowest importance coefficient was related to the components of being directional, being profound, being strong, pluralism, guidance and leadership, open-mindedness, self-esteem, and satisfaction, each with a value of (0). In the content of the 10th, 11th, and 12th-grade biology textbooks (taking into account the number of chapters), a relatively balanced and uniform distribution in terms of attention to phenomenological identity components was observed. However, each of the textbooks did not equally address all components, and some components received no attention or very little attention. In the 10th- and 12th-grade biology textbooks, the highest frequency was related to the component of challenge acceptance, while in the 11th-grade biology textbook, the component of practicality had the highest frequency.